Bilateral Hydronephrosis with Recurrent Infections - I.G.N. Wila Wirya; Hariarti Hariarti (Paediatrica Indonesiana, 1979)
A case of bilateral hydronephrosis due to a congenital hereditary anomaly was reported. The operation was performed to remove the right kidney and ureter. Correction of the obstruction in the left ureter resulted in the better functioning of the left kidney, although we cannot be sure in the long run.